2020
DOI: 10.1021/acssuschemeng.0c01870
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Visual Detection of Bipyridylium Herbicides Based on Polyelectrolyte-Induced Nanoassemblies of Pyrenyl Probes

Abstract: In this work, we report a novel fluorimetric sensing system for the visual and rapid detection of bipyridylium herbicides (paraquat and diquat) using a polyelectrolyte-induced nanoassembly strategy in 100% aqueous media. This approach relies on the formation of supramolecular assemblies between a pyrenyl probe (N,N,N-trimethyl-4-(pyren-1-yl)butan-1-aminium bromide, PyBTA) and a polyelectrolyte (poly(4-styrenesulfonic acid), PSS), which could promote paraquat complexation by the synergy of noncovalent forces su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As the increasing concentrations of PQ addition, the absorption peaks at 225 nm showed a clear red shift, which implied a decrease of the π → π* transition energy. This could be speculated that the π-conjugated system was expanded owing to the formation of a new ground-state complex by the π–π stacking between FIL and PQ. , The fluorescence lifetime of the probe remained almost constant before and after the response, further suggesting that the interaction was attributed to a static quenching process in Figure c. Besides, by comparing the 1 H NMR spectra of PQ, FIL, and the FIL–PQ complex in Figure d, the signal peak changes of the FIL–PQ complex were observed.…”
Section: Resultsmentioning
confidence: 89%
“…As the increasing concentrations of PQ addition, the absorption peaks at 225 nm showed a clear red shift, which implied a decrease of the π → π* transition energy. This could be speculated that the π-conjugated system was expanded owing to the formation of a new ground-state complex by the π–π stacking between FIL and PQ. , The fluorescence lifetime of the probe remained almost constant before and after the response, further suggesting that the interaction was attributed to a static quenching process in Figure c. Besides, by comparing the 1 H NMR spectra of PQ, FIL, and the FIL–PQ complex in Figure d, the signal peak changes of the FIL–PQ complex were observed.…”
Section: Resultsmentioning
confidence: 89%
“…Three major forces stabilize the supramolecular assembly: π–π stacking, H-bonding, and hydrophobic interactions. To understand which force has played crucial role in interaction between CPy-1 and FAD, we have investigated the emission behavior of CPy-1 toward various flavin analogues with structural diversity, such as flavin adenine dinucleotide (FAD), flavin mononucleotide (FMN), riboflavin (RF), and riboflavin tetraacetate (RFTA) (Figure a). We observed that in all cases emission signal at 450 nm decreased; however, fluorescence intensity at 520 nm had increased with the increase in hydrophobicity of flavin analogues (RFTA > RF > FMN > FAD) (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electronic detection instruments are simple, low cost, and well suited for rapid biological assays. In past studies, a variety of ECL luminophores were focused on luminol, 17 bipyridylium, 18 and quantum dots (QDs). 19 These ECL luminophores are widely used in the areas of immunoassays, pharmaceutical analysis, food, and environmental detection.…”
Section: ■ Introductionmentioning
confidence: 99%